Economic Research of Transfer of Technologies for Manufacturing High-Tech Production in Russia: Bio-Fuel - KUZNETSOV, Nikolai Ivanovich; UKOLOVA, Nadezhda Viktorovna; MONAKHOV, Sergey Vladimirovich; SHIKHANOVA, Juliya Anatolyevna (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017DO - 10.14505//jemt.v8.3(19).11, 2017)
In the article the authors analyzed the features of the transfer of technologies for the production of high-tech products, the development of renewable energy production in the Russian economy. The possibilities of Russian agriculture in the production of bio-fuel are shown, the most promising directions of it are determined. The experience of the leading Russian regions in the production of bio-fuel in modern conditions is considered. The advantages and disadvantages of technologies for the production of bio-fuels of the first and second generation are determined. The study concludes that it is necessary to create and develop a new high-tech branch of the Russian economy - bio-fuel production. In the opinion of the authors, in Russia the active development of this industry will create additional incentives in the development of agriculture, will contribute to reducing environmental pollution, enhance the status of the Russian science.